IMPACT OF FOREST EXPLOITATION ON COMMUNITY ECONOMY (CASE STUDY OF SUMATERA, HARAPAN FOREST) - Sella, Olindse Aguis (Communale Journal, 2025)
Harapan Forest is a global priority area for forest habitat representing 20 percent of the remaining lowland forests in Sumatra. Most of the area in Harapan Forest is a high-value secondary natural forest that is being restored. There are many rare fauna and flora riches that are difficult to find elsewhere , such as various species of hornbills. Forest exploitation is an increasingly pressing issue in Indonesia, where this activity not only impacts the environment, but also has significant implications for the economy of society and the country. In an economic context, forest exploitation often results in large financial losses for local governments due to the loss of potential revenue from taxes and royalties as well as negative impacts on the livelihoods of communities that depend on forest resources. Forest exploitation is often seen as a solution to encourage economic growth, especially in developing countries. It can be concluded that forest exploitation is the arbitrary use and exploitation of forest resources and products, whether in the form of land, water, flora and fauna, etc., without considering aspects of sustainability in the future.